Rohingyas, a Non-Existing Nation - Kovács-Zsankó, Gyöngyvér (Pécs journal of international and European law, 2017)
Lately, the global political environment regarding migration and statelessness is clearly in the need for change. A change in the way of considering human rights protection for those who are so vulnerable that they do not have any chance to step up for their rights. Statelessness is a major problem for the international agenda itself, although its real seriousness still remains hidden. In fact, that is the case with the stateless Rohingya Muslims of Myanmar, who live in actual exile in their own country, without having any possibilities of integration into the society.